The relationship between ABO blood group and pregnancy complications - خضر سلافه; رمضان لينا; عبد الرحمن أحمد (Latakia University Journal -Medical Sciences Series, 2022)
Introduction: The ABO system is a histological system where its antigens , in addition to red blood cells ,are located on the surface of other cells and tissues in the body . There is controversial information about the relationship of the ABO system and the major pregnancy cpmplications. Objective:Determine whether the type of blood group ABO in a pregnant woman may be a risk factor for having some complications associated with pregnancy , such as : pre-eclampsia,gestational diabets , venous thromboembolism and post partum hemorrhage:. Patients and methods: A retrospective case_control study was conducted on 215 pregnant patient at Tishreen University Hospital in Lattakia between 2021-2022. RESULTS: Non-O blood groups are associated with arterial hypertension ,especially group A and AB. Group O is a protective factor from pre_eclampsia with a statistically significant difference . The incidence of gestational diabetes is higher in group O ,but without statistically significant differences . Blood group O is associated with a higher incidence of postpartum hemorrhage than non-O groups. CONCLUSION: There is a relationship between ABO blood groups and pregnancy complications mentioned in our research .